A coin hoard from the village of Popovo, southeastern Bulgaria - Miroslava Dotkova (Българско е-Списание за Археология, 2025)
The subject of this study is a hoard of Roman imperial coins currently kept in the numismatic collection of the National Archaeological Museum in Sofia. It was discovered in 1939 in the area of Popovo village, Elhovo municipality, southeastern Bulgaria. The coins had been deposited in a pot. Traces of Thracian and Roman settlements and mounds are known in this area, located in the urban territory of Hadrianopolis. The hoard is in a very good state of preservation and consists of 237 denarii from 1st–2nd c. AD, spanning a time frame from Tiberius to Trajan. The terminus post quem of the hoard is a denarius minted between the autumn of AD 116 and August AD 117. The find from Popovo comes to be one of the few coin hoards in Thrace from the 2nd c. discovered to the south of the Balkan Range. A detailed catalogue of 237 coins is presented.